Winners and Losers in Area-Based Management of a Small-Scale Fishery in the Colombian Pacific - López-Angarita, Juliana; Tilley, Alexander; Díaz, Juan M.; Hawkins, Julie P.; Cagua, E. Fernando; Roberts, Callum M. (Frontiers in Marine Science, 2018)
The Pacific coast of Colombia has some of the most extensive mangrove forests in South America. As an isolated region and one of the country’s poorest, coastal communities rely on fishing as a main source of animal protein and income. In an attempt to reverse declining trends of fisheries resources, in 2008, an Exclusive Zone of Artisanal Fishing closed to industrial fishing, was established by stakeholders in the Northern Chocó region. Here we present a case study to investigate the effects of this area-based management on fisheries productivity and catch composition. Fishery landings data from 2010 to 2013 are compared to those of a neighbouring region with no fisheries management. Catch per unit effort, mean weight landed, and number of landed individuals were calculated for mangrove and non-mangrove associated species by boat type and fishing gear. A set of mixed effects models were used to unpack the effects of multiple factors and their interactions on response variables. Results show that across fishing gears and time, mean catch per unit effort increased by 50% in the Exclusive Zone of Artisanal Fishing within 3 years. Fisheries here focused on offshore resources with 61% more fishing trips associated with motorized boats than in the unmanaged region, where fishing was predominantly in mangroves and close to the coast. This suggests that fisheries management, may have played a role in reducing pressure on mangrove resources. However, area-based management may have also driven the displacement of fishing effort by excluding industrial trawlers, which then concentrated their activity in neighbouring areas.